Are workers musicians? Kesha Sebert, Johanna Wagner and the gendered commodification of star singers, 1853–2014. Issue 2 (May 2021) - Stahl, Matt
Abstract: The legal history of pop singer-songwriter Kesha Sebert has brought to light serious problems of gender and power in the US recording industry: it remains male dominated to its core. These contemporary problems have specific historical origins. Contextualising the 2008–2014 lawsuit between two rival producers over the exclusive right to Kesha's labour power suggests that elements of Victorian gender relations and class war were baked into the doctrine on which that 21st century case turned. Drawing empirically on court documents, and analytically on perspectives from history and sociology as well as feminist legal scholarship, this paper explains the persistent vitality of a 'gendered erotic triangle' in music production. By contextualising Kesha's gendered legal triangulation, and analysing a seemingly technical quibble about the interpretation of a statute of (temporal) limitation, this paper frames the commodification of singers' labour power as central to a gendered project of class domination.